Genetic Characterization of CTX-M-2-Producing Klebsiella pneumoniae and Klebsiella oxytoca Associated With Bovine Mastitis in Japan - Tsuka, Takeshi; Ozaki, Hiroichi; Saito, Daisuke; Murase, Toshiyuki; Okamoto, Yoshiharu; Azuma, Kazuo; Osaki, Tomohiro; Ito, Norihiko; Murahata, Yusuke; Imagawa, Tomohiro (Frontiers in Veterinary Science, 2021)
CTX-M-2-producing Klebsiella oxytoca (K. oxytoca) has not received much attention in animal husbandry compared with Klebsiella pneumoniae (K. pneumoniae), a major reservoir of extended-spectrum β-lactamase (ESBL) genes. Bacteriological examinations of 1466 mastitic milk samples between October 2012 and December 2014 were conducted. Ninety-five K. pneumoniae isolates (total prevalence: 6.5%) and 81 K. oxytoca isolates (total prevalence: 5.5%) were obtained. Seventeen K. pneumoniae isolates obtained from 15 animals reared on 11 farms and 9 K. oxytoca isolates obtained from 9 animals reared on the same farm were phenotypically confirmed to be ESBL producers. All 9 ESBL-producing K. oxytoca isolates were obtained from one farm between June and November 2013 and related to a significantly (p < 0.05) higher monthly prevalence of mild mastitis (in June, August, September, October, and November 2013). Pulsed-field gel electrophoresis (PFGE) patterns of ESBL-producing K. pneumoniae isolates were distinguished from each other by more than 6-band differences except for two isolates from two animals, whereas all 9 K. oxytoca isolates showed an identical PFGE pattern. Transferability of the blaCTX-M-2 gene was found in 14 K. pneumoniae and 9 K. oxytoca isolates by conjugation analysis. Of these isolates, the blaCTX-M-2 gene was detected on plasmids belonging to the incompatibility (Inc) groups P and N derived from 5 K. pneumoniae and 9 K. oxytoca isolates, respectively, although the plasmids from the remaining 9 K. pneumoniae were untypeable. All the transconjugants exhibited elevated minimum inhibitory concentrations of ampicillin, cefotaxime, and ceftiofur compared with those in the wild-type, recipient strain. Restriction fragment length polymorphism analysis demonstrated that the IncN plasmids extracted from 8 of 9 transconjugants, which received resistance against β-lactams from K. oxytoca, showed an identical DraI digestion pattern. These results suggest that the CTX-M-2-producing K. oxytoca strain with the above-mentioned characteristics may have clonally spread within a farm, whereas the blaCTX-M-2 gene in K. pneumoniae possibly disseminated among the farms through different plasmids. Thus, monitoring of ESBL genes, including the blaCTX-M-2 gene, among causative agents of bacterial mastitis in cows can help to develop relevant treatments and control practices.